Biology - Campbell, Neil A. (The Benjamin/Cummings Publishing Company,Inc, 1996)
This book widely used as the text for introductory biology course in universities. As pre-med students, many of my friends kept this text even after they finished the intro course for future reference. Whether you're studying for the MCAT on your own or taking prep courses with Princeton or Kaplan, you will refer to Campbell for information.